1996
DOI: 10.1159/000121136
|View full text |Cite
|
Sign up to set email alerts
|

Familial Occurrence of Atretic Cephaloceles

Abstract: In this article we report the cases of an 11-year-old girl who presented with an occipital atretic cephalocele and 2 of her siblings who had similar occipital lesions. Neuroimaging studies in these three instances showed a spectrum of posterior fossa cystic malformations. The girl’s parents and a further sibling were also investigated by neuroimaging studies that proved to be normal. The familial occurrence of cephaloceles in general, and of atretic cephaloceles in particular, seems to be very rare in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…In the literature, Jalali et al [24] characterized this condition as autosomal dominant Dandy-Walker with occipital cephalocele. Three other autosomal dominant Dandy-Walker with occipital cephalocele families have also been reported from Brazil, Spain, and China [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, Jalali et al [24] characterized this condition as autosomal dominant Dandy-Walker with occipital cephalocele. Three other autosomal dominant Dandy-Walker with occipital cephalocele families have also been reported from Brazil, Spain, and China [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant Dandy‐Walker malformation and occipital cephalocele (ADDWOC) has been considered part of the Dandy‐Walker spectrum of disorders, and is characterized by variable cerebellar hypoplasia, meningeal anomalies, occipital skull defects, and typically normal neurological development (Barkovich, Millen, & Dobyns, ). ADDWOC is a rare disorder with only a few reported families in the literature (Bassuk, McLone, Bowman, & Kessler, ; Carvalho, Giuliani, Simao, Santos, & Pina‐Neto, ; Ghonge, Kanika, & Poonam, ; Martinez‐Lage, Martinez Robledo, Poza, & Sola, ; Zhao, Chi, Zhao, & Chi, ). The use of next generation sequencing technology has assisted in the identification of nidogen 1 ( NID1 ) as a potentially disease‐causing gene in a family with ADDWOC (Darbro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While the original report of this kindred focused on the atretic cephalocele, our subsequent review of brain imaging in the proband and his aVected second cousin showed Dandy-Walker malformation in addition to the cephalocele. Three other families with autosomal dominant Dandy-Walker malformation and occipital cephaloceles (ADDWOC) have been reported from Brazil, Spain, and China (Carvalho et al 2006;Martinez-Lage et al 1996;Zhao et al 2007), signifying the worldwide occurrence of this heritable disorder. Here, we further characterize the phenotype of the original Vietnamese-American kindred, map the locus to 2q36.1 by genome-wide linkage analysis, and describe an overlapping phenotype in a child with deletion of this region.…”
Section: Introductionmentioning
confidence: 99%